2015
DOI: 10.1021/acs.molpharmaceut.5b00282
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Targeted Proteomics of Pancreatic Cancer: Deoxycytidine Kinase Protein Level Correlates to Progression-Free Survival of Patients Receiving Gemcitabine Treatment

Abstract: The purpose of the present study is to identify the determinant(s) of gemcitabine (dFdC)-sensitivity in pancreatic cancer tissues of patients treated with dFdC alone and in pancreatic cancer cell lines exposed to dFdC in vitro. Protein expression levels of 12 enzymes and 13 transporters potentially involved in transport and metabolism of dFdC in pancreatic cancer cell lines and tissues were quantified by means of our LC-MS/MS-based quantitative targeted proteomics technology. Protein expression levels of deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…57 In the present study, several metabolite levels in purine and pyrimidine metabolic pathways changed in the plasma of males with OS infertility; they may reect increased oxidative stress in spermatogenesis, eventually leading to infertility. However, specic molecular mechanisms still require further study.…”
Section: -56mentioning
confidence: 57%
“…57 In the present study, several metabolite levels in purine and pyrimidine metabolic pathways changed in the plasma of males with OS infertility; they may reect increased oxidative stress in spermatogenesis, eventually leading to infertility. However, specic molecular mechanisms still require further study.…”
Section: -56mentioning
confidence: 57%
“…The k hCNT1 , k hENT1,in , k hENT1,out , and k CDA were considered variable too, in order to account for the different protein expression among subjects. They were supposed log-normally distributed with mean equal to the estimated values and coefficient of variation (CV) taken from Burt et al 38 To our knowledge, no information regarding CDA variability in tissues is present in the literature; thus, we decided to fix the CDA CV equal to the one of the pancreatic cancer, obtained from Ohmine et al 39 Parameters of the distributions are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…14 In another publication, the concentration of these enzymes in pancreatic tumor samples from 10 different subjects was measured. 39 That information was used for the in vitro to in vivo rescaling.…”
Section: Methodsmentioning
confidence: 99%
“…Transcript 34,35 and protein 36,37 levels of human equilibrative nucleoside transporter (hENT1) to predict gemcitabine efficacy against pancreatic cancer are used as a clinical marker of the drug response. While mRNA quantification is simple, poor correlation between protein expression/activity and mRNA expression is often observed because of the poor mRNA stability in tissues or posttranscriptional variability.…”
Section: Quantitative Proteomics Data Can Be Used As a Critical Predimentioning
confidence: 99%